Controversial Hohokam handstones from the Salt River Valley, Arizona - Eric Taladoire (Journal de la Société des Américanistes)
The presence and function in several Hohokam sites of controversial objects, currently described as handstones or crushers, remains an unsolved matter. Their morphology recalls similar Mesoamerican pieces, the manoplas, generally considered to be related to the ballgame. The identification of ballcourts in Hohokam sites has long been a controversial issue, but is now generally agreed on. This paper does not aim to resolve this interrogation, but rather to call attention to a problematic aspect of relationships between Mesoamerica and Oasisamerica.